2004
DOI: 10.1037/0096-1523.30.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Which Mechanical Invariants Are Associated With the Perception of Length and Heaviness of a Nonvisible Handheld Rod? Testing the Inertia Tensor Hypothesis.

Abstract: It has been suggested that the inertia tensor governs many instances of haptic perception. However, the evidence is inconclusive because other candidate mechanical parameters (i.e., invariants) were not or were insufficiently controlled for in pertinent experiments. By independently varying all candidate mechanical parameters, the authors were able to test the role of the inertia tensor relative to that of other mechanical parameters. The results showed that length perception during rod wielding is not governe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
5
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(115 citation statements)
references
References 28 publications
7
101
5
2
Order By: Relevance
“…This is in keeping with recent experimental findings in the ecological study of perception and action. Indeed, as mentioned above, recent studies have found that the detection of the same pattern in the array can result in the perception of different environmental properties at different moments in time (e.g., Kingma et al, 2004). So what a pattern in the array informs about is co-determined by the perceptual process it is participating in.…”
Section: Applying Oyama's Conception Of Information To Perception-actionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in keeping with recent experimental findings in the ecological study of perception and action. Indeed, as mentioned above, recent studies have found that the detection of the same pattern in the array can result in the perception of different environmental properties at different moments in time (e.g., Kingma et al, 2004). So what a pattern in the array informs about is co-determined by the perceptual process it is participating in.…”
Section: Applying Oyama's Conception Of Information To Perception-actionmentioning
confidence: 95%
“…One illustrative series of experiments was conducted by van de Langenberg, Kingma, and Beek (2006;Kingma, van de Langenberg, & Beek, 2004) who examined the use of mechanical invariants in dynamic touch. Dynamic touch refers to the capacity to haptically perceive object properties (e.g., weight, length, form) by simply holding the object in the hand or wielding it (see e.g., Turvey & Carello, 1995).…”
Section: Empirical Studies Of Perception Action Learning and Develmentioning
confidence: 99%
“…The rationale for using homogeneous rods was as follows: To induce recalibration, one must provide feedback based on the variable that the participants exploit; feedback based on some other variable can induce a change in the exploited variable (Withagen & Michaels, 2005). Additionally, there is a debate in the dynamic touch literature regarding what variable is exploited to perceive length (e.g., Kingma, van de Langenberg, & Beek, 2004) and sweet spot . By using homogeneous rods of the same material and the same diameter, we can circumvent this problem of what variable to feed back on.…”
Section: Apparatus and Materialsmentioning
confidence: 99%
“…This resistance is determined by the first eigenvalue of the inertia tensor (I 1 ). The smallest resistance, determined by the third eigenvalue of the inertia tensor (I 3 ), is associated with rotating a rod around its longitudinal axis (for a more thorough treatment of the inertia tensor, see, e.g., Kingma, van de Langenberg, & Beek, 2004;Turvey, 1996).…”
mentioning
confidence: 99%